Evaluation of Strength Characteristics of Cement-Stabilized Rammed-Earth Material - Sahito, Abdul Munim; Memon, Rizwan Ali; Kumar, Aneel; Bhanbhro, Riaz (Salehan Institute of Higher Education, 2025)
The traditional method of rammed-earth construction is seeing a resurgence because of its minimal environmental impact and sustainability. Numerous elements, including soil composition, compaction procedure, stabilization methods, moisture content, and ambient conditions, affect the properties of rammed-earth materials. This research work aims to investigate the strength characteristics of cement-stabilized rammed-earth material. The strength characteristics involve compressive strength and splitting tensile strength. There are four soil types involved in the casting of cement-stabilized rammed-earth, i.e., 0C100S, 10C90S, 20C80S, and 30C70S. The moisture contents used are based on the OMC of Thar Desert sand, i.e., 11.5%, 12.5%, and 13.5%. While the cement contents used are, i.e., 5%, 10%, and 15%. The number of specimens cast is equal to 216. The results of compressive strength and splitting tensile strength tests conclude that strength increases with the increase in cement content; however, the increase in moisture content decreases the magnitude of compressive strength and splitting tensile strength. The increase in clay content up to 20% increases the compressive strength; a further increase in clay content, i.e., 30%, results in a reduction of compressive strength. The splitting tensile strength increases with the increase in clay content. The maximum compressive strength equal to 13.43 MPa is achieved in the specimen, i.e., 20C80S15c, with minimum moisture content used, i.e., OMC-1% (or 11.50%). While the maximum splitting tensile strength achieved is 6.68 MPa of the specimen, i.e., 30C70S15c, with a moisture content of 11.50%.